UJI BAKTERI Escherichia coli PADA MINUMAN ES KELAPA MUDA YANG DIJUAL DI JALAN SUKA KARYA KECAMATAN TAMPAN KOTA PEKANBARU SEBAGAI RANCANGAN MODUL PADA KONSEP EUBACTERIA DI SMA KELAS X - Indah Maya Istanti; Irda Sayuti; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know the presence of the bacteria Escherichia coli on coconut ice drink that are sold in Suka Karya street Tampan district Pekanbaru city in October 2018 to May 2019. This research is an descriptive study was conducted with the 2 phases that is phase test the bacteria Escherichia coli in the lab and phase module design. The samples are taken by purposive sampling method are purchased from 3 sellers of coconut ice drink in Suka Karya street Tampan district Pekanbaru city based on criteria that assigned. Test Escherichia coli using the method Most Probable Number (MPN) with three stages of the test which consists of presumtive test, confirmative test and complete test using different growing media and incubated at 37oC temperature during 2x24 hours. The results obtained that from 3 samples examined obtained, 1 samples contaminated by Escherichia coli. Research results are then used as module design on the Eubacteria concept in senior high school class X.Key Words: Escherichia coli, Coconut Ice Drink, Module design